SEMANTIC-STRUCTURAL RESEARCH OF METAPHORS IN SCIENTIFIC TEXTS (TAMADDUN NURI JURNALI, 2025)
The article examines the semantic and structural aspects of metaphors in scientific texts. The main features of the scientific method and the role of metaphor in it are analyzed. Semantic and grammatical properties of metaphors are studied using Uzbek and English scientific texts as examples. The results show how metaphors in scientific texts serve to express scientific concepts.